Platelet-Rich Plasma Augmentation of Meniscal Repair in the Setting of Anterior Cruciate Ligament Reconstruction. Issue 12 (October 2021) - Bailey, Lane; Weldon, Matthew; Kleihege, Jacquelyn; Lauck, Kyle; Syed, Mohammad; Mascarenhas, Randy; Lowe, Walter R.
Background: The increasing incidence of anterior cruciate ligament (ACL) and meniscal injuries has led to strong interest in discovering new methods to enhance the biological healing response of these tissues. Platelet-rich plasma (PRP) contains various growth factors associated with a positive healing response, but few existing clinical studies are available to determine the risks and benefits of these therapies. Purpose: To determine the effects of intraoperative PRP on postoperative knee function and complications at 2 years after ACL reconstruction with meniscal repair. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective matched case-control study was conducted between 2013 and 2017 using a single surgeon database of 1014 patients undergoing primary ACL reconstruction with concomitant meniscal repair, resulting in 324 patients (162 PRP patients and 162 control patients) who met the study criteria. Patients were matched by age, sex, graft type, and meniscal injury. The Single Assessment Numeric Evaluation (SANE) was administered at 2 years, and injury surveillance was conducted. Secondary outcomes included the time to return to activity (months), self-reported knee function (International Knee Documentation Committee [IKDC] score), functional performance testing (knee range of motion, single-leg balance, single-leg hopping, agility testing), and postoperative complications (graft failure, infection, loss of motion [requiring repeat arthroscopy for lysis of adhesions], venous thrombosis, etc). Univariate models were used for between-group comparisons, and alpha was set at .05 for all analyses. Results: No differences were found in SANE knee function scores between the PRP and matched-control groups at 2 years (91.6 ± 11.2 vs 92.4 ± 10.6, respectively; P = .599). Additionally, no differences were reported between groups for self-reported function (IKDC score, 87.6 ± 13.3 vs 88.1 ± 12.6; P = .952), functional performance testing ( P > .05), and timing of return to activity (7.8 ± 1.9 vs 8.0 ± 1.9 months; P = .765). The PRP group demonstrated a higher rate of postoperative knee motion loss compared with the control group (13.6% vs 4.6%; P < .001). No other differences were observed in postoperative complications ( P > .05). Conclusion: The added use of intraoperative PRP did not improve self-reported knee function, functional performance, and timing of return to activity for patients undergoing ACL reconstruction with meniscal repair. Furthermore, the use of PRP may have negative consequences for regaining knee range of motion after surgery. On the basis of these data, surgeons should cautiously consider the application of PRP when planning surgery for intra-articular injuries of the knee. Registration: NCT03704376 (ClinicalTrials.gov identifier).